Begegnungen von Dada bis heute : Briefe, Dokumente, Erinnerungen. - Richter, Hans (Köln : Verlag M. DuMont Schauberg, 1973)
Arp, Hans (Jean) ; Hausmann, Raoul ; Kassak, Lajos ; Mondriaan, Piet ; Malevich, Kasimir ; Méliès, Georges ; Ernst, Max ; Cornell, Joseph ; Cocteau, Jean ; Hennings, Emmy ; Man Ray ; Calder, Alexander ; Grosz, George ; Fellini, Federico ; Tzara, Tristan ; Kiesler, Frederick ; Duchamp, Marcel ; Feininger, Lyonel ; Leger, Fernand ; Tanguy, Yves ; Bissier, Julius ; Eisenstein, Sergei Mikhailovitch
boek